A comparative study of neonatal and maternal outcome between forceps delivery and vacuum extraction - Ghosh, Subhabrata; Biswas, Pranab K.; Mani, Manik; Chaudhuri, Snehamay; De, Nirupam K. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: Aims and objectives of the study were to compare maternal and neonatal outcomes of forceps versus vacuum application in assisted vaginal delivery. Methods: This prospective study was conducted in a tertiary care hospital of West Bengal over one year. Women in labor with vertex presentation were delivered by vacuum and forceps. A total of 100 cases were included of which 50 patients selected for forceps delivery and 50 patients for vacuum extraction. The instruments were either silastic cup vacuum extractor or Wrigley`s outlet forceps. Maternal morbidity was studied in terms of cervical tears, vaginal lacerations, episiotomy extension, perineal tears, PPH, and retention of urine. Neonatal morbidity was studied in terms of Apgar score, instrumental injuries, cephalhematoma, NICU admission and the outcome was compared. Chi square test was used to analyze the data. Results: Observations maternal morbidity viz. episiotomy extension, traumatic PPH were significant in the forceps group (p=0.01). With regards to neonatal morbidity, SNCU admission were significantly higher in forceps delivery (p=0.02) and incidence of cephalohematomas were more in ventouse delivery (p=0.02). Conclusions: Vacuum and forceps should remain appropriate tools in the armamentarium of the modern obstetrician. However, ventouse may be chosen first (if there is no fetal distress) as it is significantly less likely to injure the mother.